PENERAPAN SCL (STUDENT CENTRE LEARNING) PADA MAHASISWA PRODI PIAUD STAI DARUSSALAM LAMPUNG - Anita Oktaviana; Septiani Selly Susanti; Sinta Oktavianti (AZZAHRA, 2023)
The application of the SCL (Student Center Learning) method to PIAUD STAI Darussalam Lampung students was carried out to see the results of implementing learning regarding the application of the SCL method in class. This research uses descriptive qualitative research. The results of the research on the application of the SCL (Student Center Learning) method to PIAUD STAI Darussalam Lampung students stated that students were enthusiastic about participating in learning (72.%), students were more active (45.5%), students were motivated (90.1%), students did not understand with matter (18.2%). This shows that the application of the SCL method produces effective learning in the form of cognitive (knowledge), affective (attitude) and psychomotor (skills).